Gaya Bahasa Kias dalam Lirik Lagu Kuyamu To Kaite Mirai Karya Mafumafu - Kevin Gunawan Putra; Ni Luh Gede Meilantari (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study aims to analyze and identify the use of language styles in the song "Kuyamu to Kaite Mirai." Language style refers to the technique of utilizing the richness of language, both in written works and oral communication, to create deeper aesthetic and communicative effects. In song lyrics, the use of language style becomes a crucial element that can strengthen the meaning and artistic appeal of a literary work. This research employs Gorys Keraf's language style theory as the theoretical foundation for classifying and identifying language styles. The study utilizes a descriptive qualitative research method with primary data sources consisting of the lyrics of "Kuyamu to Kaite Mirai." The qualitative approach was chosen to enable in-depth analysis of figurative language usage within the song lyrics. The research findings reveal the presence of five types of language styles employed in the lyrics of "Kuyamu to Kaite Mirai." The identified language styles include asyndeton, assonance, erotesis, metaphor, and simile. Asyndeton was found in the use of word sequences without conjunctions to create dramatic effects. Assonance was identified through the repetition of vowel sounds that create sound harmony. The esoteric figurative language style emerges in the use of the particle の at the end of sentences, indicating that this verse constitutes an interrogative sentence. Metaphors and similes are employed to create comparisons that strengthen the song's emotional meaning. The utilization of language styles in the lyrics of "Kuyamu to Kaite Mirai" functions not merely as aesthetic ornamentation, but also as a means to convey messages and emotions more effectively to listeners. This research is expected to contribute to the understanding of language style usage in popular music works and serve as a reference for similar studies in the future.